Hemostatic effect of oxidized regenerated cellulose vs. topical tranexamic acid in total knee arthroplasty—a prospective randomized controlled trial - Li, Bowei; Pan, Wenjie; Ma, Jianbing; Huang, Yuanchi (Frontiers in Surgery, 2025)
AimsThis study compared the hemostatic effects and complications of oxidized regenerated cellulose (ORC) and topical TXA in total knee arthroplasty (TKA), thus providing a reference for the use of ORC as an alternative hemostatic agent to TXA in TKA.MethodsA total of 105 patients were included in this study and randomized into blank control, ORC, and TXA groups. The primary outcomes were total blood loss, hemoglobin drop (Hb drop), transfusion rates, and incidence of thrombosis. The secondary outcomes included operation time, tourniquet duration, coagulation parameters, inflammation markers, and complication rates.ResultsTotal blood loss was 1,002.47 ± 308.58 ml and 964.68 ± 273.00 ml in the ORC and TXA groups, respectively, both significantly lower than that in the blank control group (1,168.94 ± 405.04 ml) (P1 = 0.043 and P2 = 0.014, respectively). Hb Drop was statistically insignificantly different between the ORC (36.03 ± 12.17 g/L) and TXA (34.32 ± 10.19 g/L) groups (P = 0.555). There was no statistically significant difference in transfusion rate, operation time, tourniquet duration, coagulation parameters, inflammation markers, and complication rates among the three groups.ConclusionIn conclusion, our prospective randomized controlled trial (RCT) highlights that, oxidized regenerated cellulose (ORC) can reduce postoperative invisible blood loss in total knee arthroplasty and achieve a hemostatic effect similar to topical tranexamic acid (TXA). This provides a safe and effective hemostatic option for patients with severe underlying diseases or contraindications to tranexamic acid.Clinical Trial registrationhttps://www.chictr.org.cn/bin/project/edit?pid=186370, identifier (ChiCTR2200066633).